Green tea polyphenol treatment is chondroprotective, anti-inflammatory and palliative in a mouse posttraumatic osteoarthritis model - Leong, Daniel J (Arthritis Res Ther, 2014)
INTRODUCTION: Epigallocatechin 3-gallate (EGCG), a polyphenol present in green tea, was shown to exert chondroprotective effects in vitro. In this study, we used a posttraumatic osteoarthritis (OA) mouse model to test whether EGCG could slow the progression of OA and relieve OA-associated pain. METHODS: C57BL/6 mice were subjected to surgical destabilization of the medial meniscus (DMM) or sham surgery. EGCG (25 mg/kg) or vehicle control was administered daily for 4 or 8 weeks by intraperitoneal injection starting on the day of surgery. OA severity was evaluated using Safranin O staining and Osteoarthritis Research Society International (OARSI) scores, as well as by immunohistochemical analysis to detect cleaved aggrecan and type II collagen and expression of proteolytic enzymes matrix metalloproteinase 13 (MMP-13) and A disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS5). Real-time PCR was performed to characterize the expression of genes critical for articular cartilage homeostasis. During the course of the experiments, tactile sensitivity testing (von Frey test) and open-field assays were used to evaluate pain behaviors associated with OA, and expression of pain expression markers and inflammatory cytokines in the dorsal root ganglion (DRG) was determined by real-time PCR. RESULTS: Four and eight weeks after DMM surgery, the cartilage in EGCG-treated mice exhibited less Safranin O loss and cartilage erosion, as well as lower OARSI scores compared to vehicle-treated controls, which was associated with reduced staining for aggrecan and type II collagen cleavage epitopes, and reduced staining for MMP-13 and ADAMTS5 in the articular cartilage. Articular cartilage in the EGCG-treated mice also exhibited reduced levels of Mmp1, Mmp3, Mmp8, Mmp13,Adamts5, interleukin 1 beta (Il1b) and tumor necrosis factor alpha (Tnfa) mRNA and elevated gene expression of the MMP regulator Cbp/p300 interacting transactivator 2 (Cited2). Compared to vehicle controls, mice treated with EGCG exhibited reduced OA-associated pain, as indicated by higher locomotor behavior (that is, distance traveled). Moreover, expression of the chemokine receptor Ccr2 and proinflammatory cytokines Il1b and Tnfa in the DRG were significantly reduced to levels similar to those of sham-operated animals. CONCLUSIONS: This study provides the first evidence in an OA animal model that EGCG significantly slows OA disease progression and exerts a palliative effect. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13075-014-0508-y) contains supplementary material, which is available to authorized users.